ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN TERHADAP BIAYA OPERASIONAL PENGELOLAHAN LIMBAH PADA RUMAH SAKIT PANCARAN KASIH MANADO - Ratulangi, Aldy V. J; Pangemanan, Sifrid; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The hospital is an institution engaged in the field of health, where the service provided by doctors, nurses and health experts. In its activities, hospitals use medical devices mostly made of materials that are difficult to decompose. These medical devices, when finished are used to be waste, and waste from the hospital could potentially transmit the disease. Therefore, hospitals must have a guideline on the cost of waste management, so that the existing waste can be managed properly. Environmental Accounting is present as a guide on waste management costs that can be used in waste management. The purpose of this research is to know whether GMIM Manado Pancaran Kasih Hospital has applied environmental accounting according to existing standard. The results of this study found that GMIM Pancaran Kasih Hospital has applied its environmental accounting and carried out the process of Recognition, Measurement, Recording, Presentation, and Disclosure as well as those described in Government Accounting Standards of 2010.Keywords: Environmental accounting, Costs